Osoba z niepełnosprawnością w rozmowach kazachskich rodziców z dziećmi - Kulesza, Ewa; Butabayewa, Laura (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The paper presents the issue of social transmission by Kazakh parents concerning disability, especially their knowledge of disability and content of conversations with their children. Diagnostic survey method, survey technique and the author's questionnaire with open-ended questions were used. The analysis of content of the written statements shows that the parental message in the inclusive group compared to the general population more strongly emphasizes the attitude of tolerance and nondiscrimination of the disabled peer. Research confirms the impact of social context on the knowledge, attitudes and the image of a person with a disability and these results are consistent with those of other authors.